Epac-Selective cAMP Analogs: New Tools With Which To Evaluate The Signal Transduction Properties Of cAMP-Regulated Guanine Nucleotide Exchange Factors - Holz, George G. (2007)
The identification of 2′-O-methyl substituted adenosine-3′,5′-cyclic monophosphate (cAMP) analogs that activate the Epac family of cAMP-regulated guanine nucleotide exchange factors (cAMP-GEFs, also known as Epac1 and Epac2), has ushered in a new era of cyclic nucleotide research in which previously unrecognized signalling properties of the second messenger cAMP have been revealed. These Epac-Selective Cyclic AMP Analogs (ESCAs) incorporate a 2′-O-methyl substitution on the ribose ring of cAMP, a modification that impairs their ability to activate protein kinase A (PKA), while leaving intact their ability to activate Epac (the Exchange Protein directly Activated by Cyclic AMP). One such ESCA in wide-spread use is 8-pCPT-2′-O-Me-cAMP. It is a cell-permeant derivative of 2′-O-Me-cAMP, and it is a super activator of Epac. A wealth of newly published studies demonstrate that 8-pCPT-2′-O-Me-cAMP is a unique tool with which to asses atypical actions of cAMP that are PKA-independent. Particularly intriguing are recent reports demonstrating that ESCAs reproduce the PKA-independent actions of ligands known to stimulate Class I (Family A) and Class II (Family B) GTP-binding protein-coupled receptors (GPCRs). This topical review summarizes the current state of knowledge regarding the molecular pharmacology and signal transduction properties of Epac-selective cAMP analogs. Special attention is focused on the rational drug design of ESCAs in order to improve their Epac selectivity, membrane permeability, and stability. Also emphasized is the usefulness of ESCAs as new tools with which to assess the role of Epac as a determinant of intracellular Ca(2+) signalling, ion channel function, neurotransmitter release, and hormone secretion.